Anthropologies of Hope and Despair: Disability and the Assisted-Suicide Debate. (3rd July 2018) - Elliot, David
Abstract: The physical criteria that determine who is and who is not eligible for assisted suicide imply that some lives—such as lives with disability—are less "objectively" worthwhile than others. Besides being degrading and discriminatory, this view is self-deceived. Aging makes both the nondisabled and disabled prone over time to experience increasingly serious disabilities, from impaired mobility to hearing loss. Anthropologies that undermine life with disability therefore undermine our humanity as such, risking self-hatred and misanthropy. As an alternative to this anthropology of despair, the author considers hopeful models affirmed by disability rights activists and by Christian theology.